OPTIMASI PENGATURAN STEAM UAP MENGGUNAKAN ALGORITMA GREEDY UNTUK MENDUKUNG PROSES PEREBUSAN KELAPA SAWIT - Sunanto, Sunanto; Faural Abadi (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2021)
The sterilizer station is the core station in the processing of palm fruit. Where in the process of boiling oil palm fresh fruit bunches must be in the applicable boiling standard. In order to obtain high yields. To optimize the work of the boiling station, especially in horizontal boiling vessels to avoid trouble or problems that arise during boiling, an automation system is made that can regulate the amount ofsteam pressure that enters the boiling vessel with a predetermined time so that it can adjust the inlet valve, condensate valve, exhaust valve. Where this automation system utilizes the greedy algorithm method. And in this research, the implementation, testing and results of the automation system will be carried out, on a prototype that utilizes the NodeMCU microcontroller (esp32),the Web Thinger IO, and the pressure sensor.